Effects of canagliflozin on cardiovascular and kidney outcomes and mortality in primary and secondary cardiovascular prevention: pooled analysis from the CANVAS program and CREDENCE trial. (3rd October 2022) - Ang, F; Rapattoni, W; Bajaj, H S; Mancini, G B J; Poirier, P; Sharma, A; Wong, N C; Slee, A; Levin, A; Mahaffey, K W
Abstract: Background/Introduction: Individuals with type 2 diabetes mellitus (T2DM) are at a greater risk for experiencing cardiovascular (CV) and kidney events. Canagliflozin is a sodium glucose co-transporter 2 inhibitor that has demonstrated reduction of these events in participants with T2DM with or without a history of CV disease (CVD) in both the CANVAS Program and CREDENCE trial. Purpose: To determine the pooled effects of canagliflozin on CV outcomes, kidney outcomes, and all-cause mortality in trial participants with and without a history of CVD (secondary and primary prevention, respectively). Methods: This post hoc analysis pooled individual participant data from the CANVAS Program and CREDENCE trial. The effects of canagliflozin versus placebo on time to first event for CV outcomes (major adverse cardiovascular events [MACE], which was defined as CV death, myocardial infarction [MI] or stroke; CV death; hospitalization for heart failure [HHF], and the composite of CV death or HHF), kidney outcomes (end-stage kidney disease [ESKD], doubling of serum creatinine [dSCr], and the composite of ESKD or dSCr), and all-cause mortality were assessed in participants with T2DM with or without a history of CVD. Results: Among the 14, 543 participants from the pooled CANVAS Program (N=10, 142) and CREDENCE trial (N=4401), 5667 (39%; canagliflozin, n=3128; placebo, n=2539) were in the primary prevention group and 8876 (61%; canagliflozin, n=4869; placebo, n=4007) were in the secondary prevention group. Baseline characteristics of participants in each group were generally similar. Across both primary and secondary prevention participants, no heterogeneity in the relative risk reduction of CV outcomes, kidney outcomes, and all-cause mortality with canagliflozin versus placebo was observed (all P interaction >0.624; Figures 1 and 2). The benefits of canagliflozin on MACE and the composite of CV death or HHF were observed as early as 6 months into treatment in both subgroups of participants and were sustained throughout the study. Conclusions: In this pooled analysis of patient-level data from the CANVAS Program and CREDENCE trial, treatment with canagliflozin demonstrated early benefits and was associated with reduced risk of CV outcomes, kidney outcomes, and all-cause mortality, with similar results across primary and secondary prevention participants with T2DM. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Janssen, Inc.